76‐2: Development of Custom Shaped OLED Display. Issue 1 (28th June 2022) - Wu, Zhongyuan; Sun, Li; Xu, Pan; Yuan, Zhidong; Zhou, Bin; Liu, Jun; Li, Huihui; Wang, Huifeng; Ma, Kaihong; yang, Fei; Li, Yongqian; Shih, Huaiting; et al.
Abstract : We presented custom shaped OLED display prototype. It can meet the customer's personalized requirement to develop the nonregula shaped display with very low cost and high speed. The custom shaped OLED display is based on the LTPS backplane and inkjet printing process. We create a design methodology with specific pixel, driver circuit and fanout design rule. Also, the optical compensation method is upgraded to fit with non‐regular shape display. It can improve the display quality effectively.